The Former “Yugoslavia Tribunal” as Monument of Justice: History, Heritage and Memory of the ICTY and IRMCT in the City of Peace and Justice - van der Laarse, Rob; Jeurgens, Charles; Tanovic, Sabina (Amsterdam University Press, 2025)
After Nuremberg, there is probably no other place where the future of Europe has been so definitively tested and safeguarded as in The Hague. The iconic building of the former International Criminal Tribunal for the former Yugoslavia (ICTY) has become a global symbol of international law and transitional justice since its establishment in 1993. As the direct successor to the International Military Tribunal of Nuremberg in 1945-1946, this UN tribunal concluded 25 years of unprecedented success in investigating and trying all major war crimes suspects from the wars in the former Yugoslavia during the 1990s. It also made history through the first application of the UN Genocide Convention in the trial of the 1995 Srebrenica massacre. This report addresses the question of how the significance of the International Criminal Tribunal for the former Yugoslavia, as a heritage and memorial site for its many (inter)national stakeholders, can be preserved following the withdrawal of the UN and a possible redevelopment of the site.